Pengaruh Edukasi Melalui Media Video Animasi Terhadap Tingkat Pengetahuan Ibu Hamil Primipara Tentang Ketuban Pecah Dini Di Puskesma Lenek - Mika Utami Ekananda; Baiq Yuni Fitri Hamidiyanti; Ni Putu Dian Ayu Anggraeni (Midwifery Care Journal, 2026)
Premature rupture of membranes is a serious pregnancy complication that can lead to infection, preterm delivery, and increased maternal and neonatal morbidity. Primigravida women lack sufficient knowledge to identify early warning signs and understand proper prevention and management strategies. This study aims to determine the effect of health education using animated video media on the knowledge level of primigravida mothers regarding premature rupture of membranes at Lenek Public Health Center. The research design employed experimental one-group pretest-posttest approach. A total of 42 primigravida women were selected using purposive sampling. Data collection was carried out through a structured questionnaire given before and after the educational video intervention. The video included information about the definition, causes, risk factors, symptoms, and prevention of premature rupture of membranes. The results showed a significant improvement in participants knowledge levels following the intervention. Prior to the education, most respondents had a low level of knowledge, whereas post-intervention data indicated that the majority had good knowledge. Statistical analysis used the Chi-Square test produced a p-value of 0.000, confirming a statistically significant relationship between the animated video intervention and improved maternal knowledge. The findings demonstrated that animated video media was an effective and engaging method for delivering health education to pregnant women, especially for topics involving complications such as premature rupture of membranes. It stimulated visual and auditory learning, enhances comprehension, and promotes better retention of information. Therefore, the used of animated educational videos was recommended as part of routine antenatal care to improve maternal awareness and preparedness.